Kekerasan Terhadap Golongan Tionghoa pada Masa Revolusi di Malang, 1945–1949 - Geza Surya Pratiwi (Universitas Gadjah Mada, 2022)
This article discusses mass-violence during the revolutionary period directed to the Chinese, who were considered to have received economic and political benefits during the colonial period. It aims to examine the roots of violence perpetrated against the Chinese since the Dutch colonial period in the city of Malang. To do so, this study uses primary sources such as archives, newspapers and photographs that were produced during the revolutionary period. In addition, this study also collected oral history through interviews with the survivors and other related parties. Based on the conducted research, it was found out that the violence against the Chinese during the revolution period in Malang occurred as a result of the accumulation of anger among the local population over the injustice policy of the colonial government benefitting the Chinese economically as well as politically.